2019
DOI: 10.1186/s12891-019-2703-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of knee extensor strength measurements using a portable dynamometer anchoring system in a supine position

Abstract: Background Muscle strength measurements using hand-held dynamometry (HHD) can be affected by the inadequate strength of the tester and lack of stabilization of the participants and the device. A portable HHD anchoring system was designed that enabled the measurement of isometric knee extensor muscle strength in a supine position. This can be used with individuals who are unable to assume the sitting position required for the measurement of knee extensor strength in conventional isokinetic dynamome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 39 publications
(48 reference statements)
1
39
0
Order By: Relevance
“…The angle of 35° was chosen keeping in mind previous study results, which reported that high-level surface electromyography activity was observed when the knee joint was flexed at 35° [ 14 ]. Studies measuring knee extensor strength with the knee joint flexed at 35° in the HHD test showed good reliability [ 9 , 13 , 15 ]. Four U-shaped rings were placed on the corners of the frame to connect the belts for fixing the device to the bed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The angle of 35° was chosen keeping in mind previous study results, which reported that high-level surface electromyography activity was observed when the knee joint was flexed at 35° [ 14 ]. Studies measuring knee extensor strength with the knee joint flexed at 35° in the HHD test showed good reliability [ 9 , 13 , 15 ]. Four U-shaped rings were placed on the corners of the frame to connect the belts for fixing the device to the bed.…”
Section: Methodsmentioning
confidence: 99%
“…Four U-shaped rings were placed on the corners of the frame to connect the belts for fixing the device to the bed. The thighs of the participants can be fixed using a Velcro strap to minimize hip flexion movement [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations